2006
DOI: 10.1093/ps/85.6.980
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms of the Insulin Gene with Chicken Early Growth and Fat Deposition

Abstract: Growth rate, body composition, and fat deposition are important traits in chickens. Insulin plays important roles in hepatic cells, muscle cells, and adipose tissue cells. The purpose of the present study was to analyze association of the insulin (INS) gene with chicken growth and body composition traits. Using a F2 design resource population constructed with the crossing of Chinese native Xinghua chickens and White Recessive Rock chickens, the association of 4 single nucleotide polymorphisms (SNP; A+428G, C+1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
14
0
4
Order By: Relevance
“…In chicken, genomic sequences encoding myeloid leukemia factor 1 (MLF1) and MLF2 were identified by bioinformatics approaches. Poultry QTL mapping studies were initially undertaken to identify genes associated with economically important traits such as growth rate, feed efficiency, egg production, carcass characteristics, and disease resistance (Liu et al, 2001;Lei et al, 2005;Qiu et al, 2006). For infectious diseases, numerous genes that control the response of chickens to Salmonella have been identified by SNP analysis (Hu et al, 1997;Mariani et al, 2001;Beaumont et al, 2003;Hasenstein et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In chicken, genomic sequences encoding myeloid leukemia factor 1 (MLF1) and MLF2 were identified by bioinformatics approaches. Poultry QTL mapping studies were initially undertaken to identify genes associated with economically important traits such as growth rate, feed efficiency, egg production, carcass characteristics, and disease resistance (Liu et al, 2001;Lei et al, 2005;Qiu et al, 2006). For infectious diseases, numerous genes that control the response of chickens to Salmonella have been identified by SNP analysis (Hu et al, 1997;Mariani et al, 2001;Beaumont et al, 2003;Hasenstein et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…SNPs of GH (Feng et al 1997), GHR (Feng et al 1997(Feng et al , 1998, IGF-I and -II genes (Amills et al 2003;Yan et al 2002) have been reported to be associated with chicken growth, feeding, and egg-laying traits. Qiu et al (2006) found that variation in the insulin gene was significantly associated with the early growth of chickens. Some of the above-mentioned genes could cause bias of the visfatin gene's effect, because of segregation in the F 2 population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, application of molecular genetics in livestock breed selection for improvement of a number of important production traits has allowed obtaining better selection performances than phenotypes-only based methods. The selection based on candidate genes not only improves the selection of the favorable alleles, but also significantly shortens the selection time (Dekkers, 2004;Nadaf et al 2007;Qiu et al, 2006;R. Jiang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al, 2004). The chicken insulin (INS) and growth hormone (GH) genes are among the candidate genes for growth performance in chickens (Lei et al, 2007;Nie et al, 2005;Qiu et al, 2006;Zhang et al, 2007). Insulin is a peptide hormone secreted by the β cells of the pancreatic islets of Langerhans.…”
Section: Introductionmentioning
confidence: 99%